Evaluation of Genotype Diversity in Oat Germplasm and Definition of Ideotypes Adapted to the Mediterranean Environment - Anna Iannucci; Pasquale Codianni; Luigi Cattivelli (International Journal of Agronomy)
Oat (Avena sativa L.) is a cereal species widely used for human food and livestock feed. It is rich in primary metabolites (e.g., protein, carbohydrate, and fibre) as well as in many secondary compounds (e.g., fructo-oligosaccharides). A germplasm evaluation was carried out to determine the genetic diversity, using univariate and multivariate analyses, and to define an oat ideotype for grain and fodder production adapted to the Mediterranean environment. A total of 109 genotypes were studied under field conditions in Foggia (southern Italy) over two growing seasons (2008-2009 and 2009-2010). All of the accessions were characterised according to 13 bioagronomic traits. Accessions were very different for these evaluated traits, with wide variabilities found particularly for seed yield and fructo-oligosaccharide concentration (CV = 37%). Principal component analysis showed that the first six axes accounted for 81% of the variability. Productivity characteristics and heading time were the major sources of diversity among these oat populations. Clustering entries identified nine groups based on their morphological and agronomic properties. The relationships found among traits can help to determine which groups of genotypes are better adapted to specific environmental conditions and to identify ideotypes for developing varieties for different purposes such as for food or forage.